Delayed Presentation of Isolated Grade III Pancreatic Injury - a Case Report - Ferreira, MJ (2023)
Because of their vague and subtle indications and symptoms, pancreatic injuries are frequently misdiagnosed. It's crucial to have a high level of clinical suspicion. The presence of other organ solid lesions and vascular injuries, as well as the patient's hemodynamic condition, will determine how these injuries are treated. A surgical approach is mandatory when a ductal disruption occurs. The case of a 32-year-old man who experienced an upper abdominal blunt trauma is presented. He was admitted to our hospital with an acute abdomen 48 hours later. A complete transection of the major pancreatic duct was discovered during surgical investigation, and a distal pancreatectomy with en bloc splenectomy was performed. Even in a delayed context, distal pancreatectomy can be safely performed and is the best option.